Resistance to death pathway induction as a potential targeted therapy in CRISPR/Cas-9 knock-out colorectal cancer cell lines - Adamiec-Organisciok, Malgorzata; Wegrzyn, Magdalena; Cienciala, Lukasz; Magate, Ngoni; Skonieczna, Magdalena; Nackiewicz, Joanna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2024)
Regulated cell death is a fundamental biological process that plays a crucial role in maintaining tissue homeostasis and eliminating damaged or unnecessary cells. Ferroptosis is an iron-dependent process, characterized by the accumulation of oxidized and damaged lipids, which leads to programmed cell death. Among the ferroptotic pathway genes regulating this process, GPX4, TFRC, ACSL4, FSP1, SLC7A11, and PROM2 could be considered. There are many well-known ferroptotic pathway regulators, which are discussed in this compact review. Cells with tissues of different origin display sensitive or resistant phenotypes to such regulators. In some cases, unexpected changes during cell treatment occurred, suggesting the possibility of regulating the death pathway. We assumed that possible changing of ferro-sensitivity to ferro-resistance in cells, especially in colorectal cancer cell lines, is responded for induced chemoresistance. Using novel techniques, such as CRISPR/Cas-9 genome editing, an induced phenotype “switching” is possible.